Efektivitas Model TGT berbantuan Media QuiPrak dalam Meningkatkan Pemahaman Konsep IPAS Siswa SD - Cholida Azzahro; Erik Aditia Ismaya; Fina Fakhriyah (Universitas Ngudi Waluyo, 2026)
Abstract This study aims to measure the effectiveness of the Teams Games Tournament (TGT) model, supported by the QuiPrak (Question Paper Track) platform, in improving fourth-grade students’ understanding of IPAS concepts at Kedondong 1 Gajah Public Elementary School. This study employed a nonequivalent control group design. The sample consisted of 49 students selected using simple random sampling. Data collection instruments included pretest and posttest questions. Data analysis techniques included the N-Gain test and the Independent Samples t-test. The data showed that the N-Gain score for the experimental class reached 0.5958, categorized as Moderate, while the control class scored only 0.2826, categorized as Low, and the Sig. value in the Independent Samples t-test was 0.000 (< 0.05). Based on the research results, the TGT model supported by the QuiPrak media is significantly more effective in improving fourth-grade elementary school students’ understanding of IPAS concepts and process skills. Teachers are advised to implement this model and media to enhance students’ understanding of IPAS concepts. The use of the QuiPrak media also needs to be further developed to create a more enjoyable and meaningful learning environment. Abstrak Penelitian ini bertujuan untuk mengukur efektivitas model Teams Games Tournament (TGT) berbantuan media QuiPrak (Question Paper Track) dalam meningkatkan pemahaman konsep IPAS siswa kelas IV SD Negeri Kedondong 1 Gajah. Penelitian ini menggunakan Nonequivalent Control Group Design. Sampel penelitian berjumlah 49 siswa yang ditentukan melalui teknik Simple Random Sampling. Instrumen pengumpulan data menggunakan soal pretest dan posttest. Teknik analisis data menggunakan uji N-Gain dan uji Independent Sample t-test. Data menunjukkan skor N-Gain kelas eksperimen mencapai sebesar 0,5958 dengan kategori Sedang, sedangkan kelas kontrol hanya sebesar 0,2826 dengan kategori Rendah, serta nilai Sig. pada uji Independent Sample t-test sebesar 0,000 (< 0,05). Berdasarkan hasil penelitian, model TGT berbantuan media QuiPrak secara signifikan lebih efektif meningkatkan pemahaman konsep IPAS serta keterampilan proses siswa kelas IV SD. Guru disarankan menerapkan model dan media ini untuk meningkatkan pemahaman konsep IPAS. Penggunaan media QuiPrak juga perlu dikembangkan lebih lanjut guna menciptakan suasana pembelajaran yang lebih menyenangkan dan bermakna.